Extensive palatal swelling and asymptomatic pulp necrosis in a patient with sickle cell trait: A new case report - de-Lima, Nahida Sarhan; Matos, Lídia Roth; Matos, Danilo Barreto; Dantas, Juliana Borges de Lima; Torregrossa, Vinicius Rabelo (Journal of Oral Diagnosis, 2021)
Although sickle cell trait (SCT) has been seen as a benign condition over time, data are accumulating of serious complications due to red cell sickling enhanced by hypoxia, acidosis, dehydration, increased blood viscosity, and hypothermia. Asymptomatic pulp necrosis (APN) is a commonly reported oral complication in patients diagnosed with sickle cell disease. However, no data are associating APN in SCT patients. We report a clinical case of an extensive palatal swelling secondary to multiple APN in a patient with SCT. A 37-year-old woman diagnosed with SCT was referred for evaluation of a year-long expanding palatal swelling of the left anterior maxilla. Clinical examination revealed a negative response to the cold test in two intact permanent teeth associated with the lesion, which were referred to endodontic treatment. After that, an exploratory biopsy of the region was performed, which consisted of enucleation and curettage of all the periapical tissue. Histopathological examination confirmed the hypothesis of a periapical granuloma secondary to APN. A degree of clinical suspicion is required by dentists when pulpal necrosis of unknown origin is presented by patients with SCT.